ANALISIS EMPIRIS ATAS FAKTOR-FAKTOR YANG MEMPENGARUHI UNDERPRICING DAN KINERJA PERUSAHAAN PASCA IPO DI BURSA EFEK INDONESIA PADA TAHUN 2007-2011 - , Nazra Aulia Nazar, I Wayan Nuka Lantara, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to analyze the performance of the company stock after the Initial Public Offering (IPO) in the period of short-term and long-term, identifying period in which investors can obtain optimal benefits subsequent to the IPO and to identify factors that affect the company subsequent to the underpricing IPO. Independent variables used in this study are firmâs size, firmâs profitability (ROA), firmâs age, market trend and government ownership. Dependent variable used in this study is underpricing. The samples in this study are all companies that listed in Indonesia Stock Exchange (IDX) and experienced underpricing in his initial return from 2007 to 2011. This study using paired-samples t test and multiple linear regression to analyze the data. The results of this study indicate that there is no difference between the stock price performance of short-term period with a long-term period. The results of the identification of factors that influence the underpricing companies showed that firmâs size, firmâs profitability, firmâs age and government ownership does not have a significant effect on underpricing, while the market trend has a positive effect on underpricing.